Linear Systems : Non-Fragile Control and Filtering - Yang, Guang-Hong ... [et al.] (Boca Raton : CRC Press, 2013)
Designing controllers/filters such that the resulting closed-loop systems are non-fragile or insensitive with respect to the perturbations in the controller or filter coefficients has become an important research topic in many fields of engineering and science. This book develops a systematic presentation of the newly proposed methods for non-fragile/insensitive control/filtering of linear systems with respect to controller/filter coefficient variations. It provides designs and guidelines that can be used to develop advanced non-fragile control techniques to improve reliability, maintainability, and survivability of complex control systems--
1. Introduction -- 2. Preliminaries -- 3. Non-fragile state feedback control with norm-bounded gain uncertainty -- 4. Non-fragile dynamic output feedback control with norm-bounded gain uncertainty -- 5. Robust non-fragile kalman filtering with norm-bounded gain uncertainty -- 6. Non-fragile output feedback control with interval-bounded coefficient variations -- 7. Non-fragile H8 filtering with interval-bounded coefficient variations -- 8. Insensitive H8 filtering of continuous-time systems -- 9. Insensitive H8 filtering of delta operator systems -- 10. Insensitive H8 output tracking control -- 11. Insensitive H8 dynamic output feedback control.
Includes bibliographical references and index.
Also available in print edition.
Mode of access: World Wide Web.
Keywords: Linear control systems; Electronic books